2006
DOI: 10.1007/s00068-006-5081-x
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Bipartite Patella Fracture with Quadriceps Rupture

Abstract: Bipartite patella fracture with quadriceps rupture is an unusual injury. It is quite often mistaken as an avulsion fracture of patella, and the X-ray of contra-lateral knee is useful for diagnosis, and appropriate treatment should be decided at the time of surgery. We report a single case of this entity in which bipartite patella fracture was misdiagnosed initially as a patellar fracture. IntroductionThe secondary ossification centre of patella that fails to coalesce with the primary ossification centre result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…These findings are not related to patellar fracture. Fourth, several features of the x‐ray films can help to differentiate bipartite patella from patella fractures: the bipartite patella is frequently bilateral; it is usually without soft tissue swelling of the knee joint; it usually consists of a large main bone and a small bone which is usually situated at the superolateral aspect of the patella; the radiolucent line of demarcation is wide, runs downward and lateral, and has a round sclerotic margin, not a fracture line; the opposing bony margins are smooth, dense, and can be seen to be composed of bone cortex; there is no periosteal reaction and bone callus formation; and consolidation will not occur by treatment. Reconstruction CT scans, magnetic resonance imaging, and bone scintigraphy can also help us to differentiate bipartite or multipartite patella from patella fracture, and MRI is currently thought to be the most appropriate method applied to evaluate patients with bipartite patella .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are not related to patellar fracture. Fourth, several features of the x‐ray films can help to differentiate bipartite patella from patella fractures: the bipartite patella is frequently bilateral; it is usually without soft tissue swelling of the knee joint; it usually consists of a large main bone and a small bone which is usually situated at the superolateral aspect of the patella; the radiolucent line of demarcation is wide, runs downward and lateral, and has a round sclerotic margin, not a fracture line; the opposing bony margins are smooth, dense, and can be seen to be composed of bone cortex; there is no periosteal reaction and bone callus formation; and consolidation will not occur by treatment. Reconstruction CT scans, magnetic resonance imaging, and bone scintigraphy can also help us to differentiate bipartite or multipartite patella from patella fracture, and MRI is currently thought to be the most appropriate method applied to evaluate patients with bipartite patella .…”
Section: Discussionmentioning
confidence: 99%
“…KEYWORDS: forensic science, forensic medicine, forensic identification, bipartite patella, misdiagnosed, patella fracture Bipartite patella is recognized as a developmental anomaly of ossification and is usually found by an incidental radiography (1,2). Gruber was the first to report a case of bipartite patella in 1883 (3), and he found that both patellae of a 21-year-old farmer were divided into a large lower inner fragment and a small upper outer fragment.…”
mentioning
confidence: 99%
“…The occurrence of bipartite patella simultaneously with quadriceps avulsion is an uncommon injury which is often misdiagnosed as a patellar avulsion fracture [1].…”
Section: Discussionmentioning
confidence: 99%
“…Bipartite patella occurs when the secondary ossification centre of the patella fails to fuse with the primary center [1]. It has an incidence of 2-6%, with males having a higher predisposition rate (8:1) [2].…”
Section: Discussionmentioning
confidence: 99%
“…Patella embriyolojik olarak 8. haftada diz boşluğu ve kas taslağından önce, kuadriseps taslağının altında oluşur. Araştırmalara göre patella genelde (%75) tek bir ossifikasyon merkezinden gelişmektedir (2,3). Primer ossifikasyon merkezi kızlarda 21--54. aylar arasında erkelerde ise 36--72. aylar arasında ortaya çıkmaktadır (2).…”
Section: Introductionunclassified